Feeding strategy with alternate fasting and refeeding: effects on farmed pacu production - Takahashi, L. S. [UNESP]; Biller, J. D. [UNESP]; Criscuolo-Urbinati, E. [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Wiley-Blackwell, 2011)
P>A 36-day trial was conducted to determine the effects of repetitive periods of food restriction and refeeding on growth and energy metabolism in pacu (Piaractus mesopotamicus). A total 264 juvenile fish (36.9 +/- 2.8 g) were fed with the experimental diet for 36 days using three regimes: (i) feeding daily to satiation (FD); (ii) no feed for 3 days, then feeding the same amount offered to the control groups for the next 3 days (NF/R controlled); and (iii) no feed for 3 days, then feeding to apparent satiation for the next 3 days (NF/R at satiation). The treatments were distributed into four tanks each. WG and SGR were higher in FD group. Fish refed showed hyperphagia just up to the second day of refeeding. The worst feed conversion rate and the lowest protein efficiency ratio were found in fish NF/R controlled. The lowest values of visceral fat somatic index were found in both fasted fish groups, particularly in NF/R at satiation. The LL and glycogen concentrations, and the hepatosomatic index were all elevated in both feed restricted fish. Muscle lipid showed a tendency to decrease after the cycle of fasting and refeeding. Plasma free fatty acids and glucose levels were elevated in fish subjected to feeding restrictions while serum triglycerides levels were reduced. Triiodothyronine levels were significantly depressed in fish from the NF/R-controlled group and remained at the same levels as the control fish in fish NF/R at satiation. Results indicated that fish subjected to cyclic periods of 3-day satiation or controlled feeding after 3-days of fasting were unable to achieve the final body weight of fish fed to satiation after 36 days.
Keywords: feeding management; starvation; hyperphagia; energy metabolism